Stakeholder engagement infrastructure to support multicenter research networks: Advances from the clinical research networks participating in PCORnet. Issue 1 (12th May 2022) - Cope, Elizabeth L.; McTigue, Kathleen M.; Forrest, Christopher B.; Carton, Thomas W.; Fair, Alecia M.; Goytia, Crispin; Harrington, Joseph M.; Lowe, Susan; Merritt, J. Greg; Shenkman, Elizabeth A.; Stephens, William J.; Templeton, Anna; et al.
Abstract: Background: The evidence based on the inclusion of patients and other stakeholders as partners in the clinical research process has grown substantially. However, little has been reported on how stakeholders are engaged in the governance of large‐scale clinical research networks and the infrastructure used by research networks to support engagement in network‐affiliated activities. Objectives: The objective was to document engagement activities and practices emerging from Clinical Research Networks (CRNs) participating in PCORnet, the National Patient‐Centered Clinical Research Network, specifically regarding governance and engagement infrastructure. Methods: We conducted an environmental scan of PCORnet CRN engagement structures, assets, and services, focusing on network oversight structures for policy development and strategic decision‐making. The scan included assets and services for supporting patient/stakeholder engagement. Data were collected by searching web‐based literature and tool repositories, review of CRN Engagement Plans, analysis of previously collected key informant interviews, and CRN‐based iterative review of structured worksheets. Results: We identified 87 discrete engagement structures, assets, and services across nine CRNs. All CRNs engage patients/stakeholders in their governance, maintain workgroups and/or staff dedicated to overseeing engagement strategies, and offer one or more services to non‐CRN researchers to enhance conducting engaged clinical research. Conclusions: This work provides an important resource for the research community to explore engagement across peers, reflect on progress, consider opportunities to leverage existing infrastructure, and identify new collaborators. It also serves to highlight PCORnet as a resource for non‐CRN researchers seeking to efficiently conduct engaged clinical research and a venue for advancing the science of engagement.